Factors That Influence Work Quality - Alex Stepanus Sinaga, Richard; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study aims to analyze the impact of compensation on work motivation and work quality at BPJS Ketenagakerjaan Regional Office of North Sumatra. Compensation is considered a critical factor influencing employee work motivation, which in turn affects work quality. This quantitative research involves a saturated sample of 80 permanent employees. Data were collected using questionnaires, and the analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that compensation has a positive and significant effect on work quality but does not significantly affect work motivation. Moreover, work motivation positively and significantly impacts work quality. Compensation also indirectly influences work motivation through work quality. These findings provide important implications for company management in efforts to improve work quality through appropriate compensation policies and maintaining employee motivation.